Local Resources Management to Support Activities Utilization of Yard Land in Wagir District, Malang Regency: Pengelolaan Sumberdaya Lokal untuk Menunjang Kegiatan Pemanfaatan Tanah Pekarangan di Kecamatan Wagir Kabupaten Malang - Parmawati, Rita (LPPM Universitas Yudharta Pasuruan, 2023)
Sumbersuko Village is one of the villages in the Wagir District, Malang Regency. This village is a village located in a mountainous area, including one area at the foot of Mount Kawi where approximately 60 percent of the area is a coffee plantation area. The purpose of carrying out this community service activity is to be able to develop community awareness so that they are willing and able to use their yard as a source of food and nutrition and process coffee waste. The method offered is in the form of direct assistance by providing counseling and training related to chemistry and waste treatment such as the manufacture of Liquid Organic Fertilizer and Eco-Enzyme. The result was that the Study Center Team Outside the Main Campus Universitas Brawijaya Kediri succeeded in opening the motivation of farmers to do better farming, especially in the utilization of their yards as well as the efficiency of garden crops in this case smallholder coffee plantations. In addition, the processing of coffee skin waste into Eco-Enzyme in the form of Liquid Organic Fertilizer can be used directly by the community as a solution to reduce production costs. Therefore, it is hoped that in the future the results of this activity can be optimally utilized to realize the success of organic coffee processing.